The quasar M-BH-M-host relation through cosmic time - II. Evidence for evolution from z=3 to the present age - Decarli R; Falomo R; Treves A; Labita M; Kotilainen JK; Scarpa R (WILEY-BLACKWELL, 2022)
We study the dependence of the M-BH-M-host relation on the redshift up to z = 3 for a sample of 96 quasars, the host galaxy luminosities of which are known. Black hole masses were estimated assuming virial equilibrium in the broad-line regions, while the host galaxy masses were inferred from their luminosities. With these data, we are able to pin down the redshift dependence of the M-BH-M-host relation along 85 per cent of the Universe age. We show that, in the sampled redshift range, the M-BH-L-host relation remains nearly unchanged. Once we take into account the ageing of the stellar population, we find that the M-BH/M-host ratio (Gamma) increases by a factor of similar to 7 from z = 0 to z = 3. We show that Gamma evolves with z regardless of the radio loudness and of the quasar luminosity. We propose that the most massive black holes, living their quasar phase at high redshift, become extremely rare objects in host galaxies of similar mass in the Local Universe.